Writing Assessment in EFL Classroom of Senior High School - Sugiyarni; Setia Rini (UNIB Press, 2023)
This study examines the concept of assessment as an important educational practice for improving teaching and learning processes. In particular, it focuses on the strategies and techniques used in assessing writing comprehension in relation to her EFL education in secondary school. There are several previous studies evaluate writing with Authentic Tests like the studies written by (Bin Abdul Aziz & Yusoff, 2016; Idham, F. I., Nadrun, 2015; Masrul, 2017; Natalia et al., 2018; Saputra & Marfuah, 2022; Sari et al., 2019; Sundusiah et al., 2019). Unlike previous studies, this study describes writing assessment, designing writing assessment, and the scoring method. In this way, teachers can apply appropriate techniques and use assessment results to modify teaching and improve learning skills, especially in writing classes.